The power of mass media in literature development in Indonesia - Dedi Pramono; Dani Fadillah (Universitas Negeri Yogyakarta, 2023)
This study aims to reveal how the mass media has a very large role to develop literature in Indonesia. This is important to mention considering that literature is one of the signs of a nation's civilization, therefore support from various directions for developing literature is very meaningful. With this research, it is hoped that the world of Indonesian literature can further develop in the future, especially through the role of the mass media. This research was conducted using a qualitative approach, the data was collected through interviews and a comprehensive review of documents. The data obtained is then reduced and compiled into a scientifically justifiable research report. The results of this study show that the contribution of the mass media is very large in the development of literature in Indonesia. Literature in Indonesia has an important role in the national identity as an international exchange. Literature can be called the nation, language, and literature which has become the glue between a country